The role of albumin-corrected anion gap as a predictor of all-cause mortality in patients with Sepsis-AKI: A propensity score-matched cohort study. - Jian Liao; Xiao Xiao; Dingyu Lu; Maojuan Wang; Wei Huang (PLoS ONE, 2025)
Background The potential association between albumin-corrected anion gap at admission and prognosis in patients with sepsis-induced AKI remains uncertain. The purpose of this study was to explore the prognostic value of ACAG on mortality in patients with Sepsis-AKI. Methods Data for this retrospective study were obtained from the MIMIC IV2.2 database. We used propensity score matching (PSM) and Cox proportional hazards regression analysis to evaluate the correlation between the ACAG and clinical outcomes in patients with Sepsis-AKI. Propensity score matching (PSM) analysis was conducted to minimize bias. Receiver operating characteristic curves were generated for albumin, AG, and ACAG, and comparisons of the areas under the ROC curves were made. Decision curve analysis (DCA) was carried out to assess the net benefit of ACAG. Results According to the screening criteria, we identified a cohort of 2387 patients diagnosed with Sepsis-AKI. When comparing the normal-ACAG group(12-20 mmol/L) to the high-ACAG group(>20mmol/L)), it was found that the high-ACAG group exhibited longer stays in the ICU(5 days vs.4 days, P = 0.023) and higher hospital mortality rate(48.5% vs. 20.2%, P < 0.001). After matching, Cox regression analysis results showed that the high-ACAG group exhibited higher risk of hospital mortality (HR = 1.80, 95%CI: 1.27-2.56, P < 0.001). The area under the curve (AUC) values of ACAG was 0.697 (after PSM), which was significantly higher than those of albumin or AG. ACAG also had the highest Youden's index and the largest net benefit range according to the decision curve analysis (DCA). Conclusion Elevated serum ACAG (>20 mmol/L) is an independent risk factor for all-cause hospital mortality in patients with Sepsis-AKI. ACAG can be a new and easily acquired indicator that can provide new ideas for clinical practice.